2020
DOI: 10.1515/rams-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous enhancement of strength and ductility with nano dispersoids in nano and ultrafine grain metals: a brief review

Abstract: Grain refinement is the most universal and effective method of strengthening metallic materials, which is known as the “Hall-Petch” relationship. However, when grain size is refined to sub-micro regime (Ultrafine Grain, UFG) or even nano regime (Nano Grain, NG), the plasticity of metallic materials becomes poor. Massive studies indicate that the low strain hardening ability resulted from the enhanced dynamic recovery and lack of dislocation accumulation in fine grains is the main reason for low ductility in UF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Grain-refining strengthening [56] is to improve strength by reducing grain size. Because the external force can be dispersed in more grains when the fine-grained copper is deformed under force, the plastic deformation is relatively uniform and the stress concentration is lower.…”
Section: Ultrafine Grained Copper and Copper Alloysmentioning
confidence: 99%
“…Grain-refining strengthening [56] is to improve strength by reducing grain size. Because the external force can be dispersed in more grains when the fine-grained copper is deformed under force, the plastic deformation is relatively uniform and the stress concentration is lower.…”
Section: Ultrafine Grained Copper and Copper Alloysmentioning
confidence: 99%
“…This approach is mentioned in this review solely to create the integrity of the review. Despite the fact that this approach has been successfully used to increase plasticity in NC Cu [61] and steel [62], it cannot be applied to UFG and NC aluminum and its alloys due to the high stacking fault energy in aluminum lattice [63]. However, it should be noted that there are few studies where the authors claim to have observed twin structures in some UFG and NC Al-alloys of the Al-Mg system [64,65,66].…”
Section: Introduction Of Nanotwinsmentioning
confidence: 99%
“…In recent decades, both the ex-situ and in-situ methods have been developed to homogeneously introduce the desirable second-phase dispersoids into different metal matrixes 13 15 . The nano dispersoids or nanoprecipitates introduced via the in-situ method are mainly synthesized through thermo-mechanical treatment or chemical reaction 15 . Thus, they generally exhibit good thermodynamic stability, fine size, and uniform distribution in metal matrix 13 .…”
Section: Introductionmentioning
confidence: 99%